Avaliação do ensino e aprendizagem na docência universitária e a formação de professores de Artes Visuais - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The object of this study is to evaluate the teaching and learning in college teaching of the Course Degree in Visual Arts from the State University of Ponta Grossa - UEPG / PR. The problem is expressed by means of the following question: What are the basics theoretical-methodological evaluation of teaching and learning in college teaching of the Course Degree in Visual Arts of the UEPG/PR? The general objective is to analyze the foundations theoretical-methodological assessment of the teaching and learning of Visual Arts, in college teaching in the critical perspective of Adorno (2009,2010), in the Course of Degree in Visual Arts of the UEPG/PR. As specific objectives of this study were listed: (A) detect the concept of evaluation of teaching and learning in the official documents of the Course Degree in Visual Arts of the UEPG/PR; (B) analyze the concept of evaluation of teaching and learning for teachers and academics from the 4th year Degree in Visual Arts of the UEPG/PR; (C) Examine the evaluation criteria and the evaluation practices of learning that professors use in the disciplines of the Course Degree in Visual Arts of the UEPG/PR. The theoretical referential consists of the following authors: Adorno (2009;2010); Barbosa (1984, 1989, 1991, 2003); Demo (1998, 2004); Freire (1989, 1997, 1999, 2005); Isaia (2003, 2005, 2006); Libâneo (1990, 2005); Luckesi (2003, 2005, 2011); Masetto (2003), Pucci (1998,2001); Saul (1992, 1995, 2008); Zimmerman (2005), among others. The research methodology is supported by a qualitative approach in a case study with routing of the dialectic method founded by Critical Theory of Adorno (2002, 2010). The data collection instruments are the questionnaires, interviews or semi structured interviews and documentary analysis. The research subjects were professors with training in Visual Arts that act in the Course of Degree in Visual Arts of the UEPG/PR and licensees of the 4th year/2016 and 4th year/2017 of that course. The data analysis was performed in accordance with the theoretical assumptions of the methodology of content analysis of Bardin (2004) and Lüdke and André (1986). The results show that the foundations theoretical-methodological evaluation of teaching and learning in college teaching of the Course Degree in Visual Arts of the UEPG/PR are for the most part based on the theory of history and criticism, with emphasis on the formative evaluation, the procedure and the diversity of evaluative instruments. However concludes that there is so much to discuss, reflect and search on the evaluation in college teaching of the Course Degree in Visual Arts, and that despite some progress, the same is still fragmentary, fragile and complex in the process of teaching and learning in teaching in Visual Arts, being required further studies to support the training of teachers to work in Basic Education.
Keywords: Avaliação em Artes Visuais; Docência Universitária; Formação de professores; Evaluation in Visual Arts; College Teaching; Training Teachers; CNPQ::CIENCIAS HUMANAS::EDUCACAO